Zootrophy (Global Journal of Human-Social Science, 2020)
The human interest in other animals has been incontrovertibly confirmed by anthropology and psychology: think of the animalist art of the Paleolithic age or the Neolithic artifacts, the processes of domestication or the first forms of religious expression, the crosscultural tendency to have domestic animals or today's beneficial animal-assisted activities. The evidence and proofs of this fact are such as to justify both a descriptive research on objectively assessable signs, and an explanatory research on their possible causes. The following essay aims to analyze the most obvious evidence of the human orientation towards other species, comparing the different theories that have tried to explain this phenomenon. Furthermore, I also want to propose a new explanatory hypothesis based on a variety of motivational orientations and able to produce some flywheel effects.
Keywords: zoophilia; biophilia; zoomorphism; theriomorphic gestalt; domestication; epimelesis